A concepção docente sobre o processo de avaliação na educação infantil em João Pessoa: uma análise na perspectiva da psicologia histórico-cultural - Souza, Valdinélia Virgulino de (2020)
This dissertation discusses the evaluation in Early Childhood Education. It is a concept with several approaches in the educational literature and its understanding persists as a challenge to teachers in school practice. To investigate this issue, we aimed to understand the teachers' conception about the evaluation process in Early Childhood Education in Early Childhood Reference Centers (CREI) in the city of João Pessoa-PB. As for the method of analysis, we used the materialist dialectic that allowed us to systematize the movement of the phenomenon in the social and empirical context through the analytical categories mediation, contradiction and totality, as well as empirical categories teaching, learning and evaluation. The technique for collecting the information was the semi-structured oral interview and simple participant observation, both developed with six preschool teachers. In the theoretical basis, we summarize two blocks of analysis, the first of which points out that the historical constructions about the evaluation of learning in Early Childhood Education in Brazil, permeate the pedagogical approaches of Traditional Education, New Education and Technicist Education, as well as, the educational policies and teaching methodologies. In these approaches, the evaluation methods are classificatory and exclusive and used to keep the subjects docile and disciplined in face of the dominant social practices. n the second block, we analyze the foundations of Historical-Cultural Psychology, conceived as an alternative for the assessment of learning in Early Childhood Education. Regarding the teachers' conceptions about evaluation in Early Childhood Education, we found several interpretations that permeate the pedagogical practice in a confused and fragmented way. A factor that may have contributed to this reality is related to the fact that, in the Brazilian scenario, the defense and theoretical studies aimed at evaluation in Early Childhood Education was conceived recently, instituted by the LDB of 1996. A factor that may have contributed to this reality is related to the fact that, in the Brazilian scenario, the defense and theoretical studies aimed at evaluation in Early Childhood Education was conceived recently, instituted by the LDB of 1996. Another determinant is based on a training that is still weakened for this level of education, both in initial training courses and in continuing training for teaching, and they still leave something to be desired for a qualified professional to teach in early childhood. Finally, to try to overcome these gaps in the teachers' conceptions and practices about evaluation, we present an alternative for a dynamic evaluation, with a view to being used as a pedagogical tool in Early Childhood Education. We emphasize that this alternative is still in the field of possibilities.